2003
DOI: 10.1002/adfm.200304360
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Green Emission in Polyfluorene‐Based Conjugated Polymers: On‐Chain Defect Fluorescence

Abstract: The low emission band at 2.2–2.3 eV in polyfluorene‐based conjugated materials is studied by various spectroscopic methods on defined copolymers of 9–9′‐difarnesyl‐fluorene with 9‐fluorenone, which can be seen as a model compound for degraded polyfluorenes. Absorption, electroluminescence, and photoluminescence in the film (temperature‐dependent) and solution (room temperature) reveal the optical properties of this low‐energy emission band emerging in polyfluorene‐type polymers upon degradation. All the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
160
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 265 publications
(179 citation statements)
references
References 27 publications
(26 reference statements)
10
160
1
4
Order By: Relevance
“…Indeed, these results show quite different behaviour compared to the effects observed previously on fluorene-based polymers, which are reported to possess red-shifting spectra mainly due to oxidative degradation after such treatment. [29][30][31][32][33][34] Our polymers, except PF, contain extra cross-linking groups, which are able to supplement the emission spectra with some red-shifted component in a positive manner when kept at a controlled level. This additional contribution on the red side of the visible spectrum is proven to be not only because of oxidative keto defect formation, but mainly due to the cross-linkable azide and bromide species on PFA and PFB, respectively.…”
Section: -33mentioning
confidence: 99%
“…Indeed, these results show quite different behaviour compared to the effects observed previously on fluorene-based polymers, which are reported to possess red-shifting spectra mainly due to oxidative degradation after such treatment. [29][30][31][32][33][34] Our polymers, except PF, contain extra cross-linking groups, which are able to supplement the emission spectra with some red-shifted component in a positive manner when kept at a controlled level. This additional contribution on the red side of the visible spectrum is proven to be not only because of oxidative keto defect formation, but mainly due to the cross-linkable azide and bromide species on PFA and PFB, respectively.…”
Section: -33mentioning
confidence: 99%
“…Fourier transform infrared (FTIR) spectroscopy has revealed that fluorenone defects, formed on degradation of PFs, are related to the intensity of the low-energy emission band (15,19,(31)(32)(33)(34)(35)(36)(37)(38). The idea that fluorenones could be responsible for the green light emission was substantiated by the synthesis of poly-and oligofluorenes containing a precise number of fluorenone moieties that exhibit green emission, even in dilute solution (24,33,(39)(40)(41). It is generally accepted that keto defects are generated in PF-type polymers by the oxidation of monoalkylfluorenes (42) and are extremely difficult to eliminate from the monomer feed and, therefore, are incorporated into the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…With further development, combined with temporal and spectral characterization, DNA-PLM can feasibly identify highly specific molecular "fingerprints," leading to in situ label-free sequencing of the genome. Additionally, topological and chemical alterations in highly condensed DNA strains can result in various additional photophysical interactions, as has been studied in polymer molecules, including energy transfer (55-57), ground-or excited-state aggregate formation (58,59), and charge transfer (60). These photophysical processes can significantly modify the molecular optical properties, allowing us to further capture functional information about the chromatin nanoarchitecture.…”
Section: Resultsmentioning
confidence: 99%